Constructing a Religious Psychosocial Model for Social-Emotional Resilience among Girls Affected by Violence in Madura - Reswari, Ardhana; Aziz, Thorik; Masuwd, Mowafg; Magfiroh, Amirin Nisa'uh (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – Psychosocial intervention models for girls affected by violence in Indonesia remain predominantly secular, overlooking the central role of religious frameworks in trauma recovery within Muslim-majority communities. This study addresses that gap by constructing an empirically grounded, religiously-informed conceptual model to strengthen the social-emotional resilience of girls affected by violence in Madura, where Islamic values, kyai, and pesantren constitute the core of community life.Design/methods/approach – A qualitative study employing Constructivist Grounded Theory (Charmaz, 2014) was conducted over four months (August–November 2025). Data were generated through in-depth interviews, participatory observation, and focus group discussions with twelve participants comprising girls affected by violence, psychologists, victim advocates, and a religious leader in Pamekasan Regency. Constructivist coding procedures were applied iteratively until theoretical saturation was achieved.Findings – Analysis yielded a core theoretical category, Spiritually-Anchored Resilience as an Integrated Recovery Process, supported by three resilience resource mechanisms corresponding to Grotberg's framework: external resources (I Have), internal strengths (I Am), and interpersonal skills (I Can), each integrated with Islamic values. These mechanisms informed a four-phase empirically constructed conceptual model stabilization, trauma processing, meaning reconstruction, and social reintegration synthesizing trauma-informed care with Islamic healing concepts of syifa' and tazkiyatun nafs. Religious leaders and pesantren were identified as significant contextual actors within the recovery ecosystem, whose roles in supporting intervention warrant further empirical investigation.Research implications/limitations – The model is bounded by its focus on Pamekasan Regency and a purposive sample of twelve participants, limiting transferability. Future research involving larger, multi-site samples is encouraged to validate and extend the model.Practical implications – Psychosocial programs in religious communities should integrate local Islamic frameworks and foster structured collaboration between mental health professionals and religious leaders, with pesantren serving as culturally trusted recovery settings.Originality/value – This study contributes an empirically derived, context-sensitive conceptual model that integrates Islamic religious values into contemporary resilience frameworks, offering a culturally responsive alternative to universalist psychosocial intervention approaches for girls affected by violence in Muslim-majority societies.Paper type Research paper